Trauma Recovery Is Cultural: Understanding Shared and Different Healing Themes in Irish and American Survivors of Gender-based Violence - Sinko, Laura (Journal of interpersonal violence, 2021)
Little research has focused on the trauma healing processes of survivors of gender-based violence (GBV) worldwide. Even less research has utilized cross-cultural comparison to understand shared or culturally-distinct healing goals, creating a gap in understanding how to provide adequate, culturally relevant, and trauma-informed care to survivors. The purpose of this study was to cross-culturally compare shared healing influences and themes of the trauma recovery process in samples of Irish and American female survivors of GBV. To gather healing data, an ethnographic narrative interview was used with 19 American and 12 Irish female survivors who self-identified as having experienced GBV. Thematic analysis was used to examine and compare desired healing outcomes, focusing on the definitions, influences, and meanings of healing experiences. Our analysis revealed shared healing objectives of reconnecting to the self, others, and the world. Within reconnecting with the self, shared themes included regaining control and feelings of competency. Within reconnecting to others, shared themes included building and maintaining relationships, living one’s life authentically, and feeling heard and understood. Within reconnecting to the world, shared themes included feelings of serenity, finding fulfillment, and having hope for a brighter future. Although these themes were shared, the way they manifested in each culture was often different. A vital component of the healing dynamic in the Irish sample was survivors’ mothering responsibilities and feelings of unconditional devotion to their children. Conversely, the American sample focused on personal growth and resolving feelings of weakness. This information reveals shared as well as cultural nuances of important healing objectives following GBV. The present study’s results can be used to create culturally sensitive and relevent healing spaces for survivors. These results can also inform intervention and messaging strategies aimed at promoting healing in these populations.